Nephrogenic Diabetes Insipidus in Childhood: Assessment of Volume Status and Appropriate Fluid Replenishment. Issue 7 (July 2020) - Guarino, Stefano; Diplomatico, Mario; Marotta, Rosaria; Pecoraro, Anna; Furlan, Daniela; Cerrone, Lorenzo; Miraglia del Giudice, Emanuele; Polito, Cesare; La Manna, Angela; Marzuillo, Pierluigi
Abstract : Abstract: Patients affected by nephrogenic diabetes insipidus (NDI) can present with hypernatremic dehydration, and first-line rehydration schemes are completely different from those largely applied in usual conditions determining a mild to severe hypovolemic dehydration/shock. In reporting the case of a patient affected by NDI and presenting with severe dehydration triggered by acute pharyngotonsillitis and vomiting, we want to underline the difficulties in managing this condition. Restoring the free-water plasma amount in patients affected by NDI may not be easy, but some key points can help in the first line management of these patients: (1) hypernatremic dehydration should always be suspected; (2) even in presence of severe dehydration, skin turgor may be normal and therefore the skinfold recoll should not be considered in the dehydration assessment; (3) decreased thirst is an important red flag for dehydration; (4) if an incontinent patient with NDI appears to be dehydrated, it is important to place the urethral catheter to accurately measure urine output and to be guided in parenteral fluid administration; (5) if the intravenous route is necessary, the more appropriate fluid replenishment is 5% dextrose in water with an infusion rate that should slightly exceed the urine output; (6) the 0.9% NaCl solution (10 mL/kg) should only be used to restore the volemia in a shocked NDI patient; and (7) it could be useful to stop indomethacin administration until complete restoration of hydration status to avoid a possible worsening of a potential prerenal acute renal failure.